Estudo de interação lectina-carboidrato por meio da técnica de microbalança de cristal de quartzo - Pedroso, Mariele Mucio (2006)
In this work a study of proteins Jacalin and Concanavalin A, belonging to the class of lectins, and the interaction with different carbohydrates was accomplished through Quartz Crystal Microbalance (QCM). The lectins were immobilized by self-assembly monolayer by means three methods. In two of them were used the cystamine and glutaraldehyde and the protein immobilized in a single layer or multilayer. In the third method, a solution of thiols, 11-mercaptoundecanoic acid and 2-mercaptoethanol, in a proportion of 1:10, and the reagents reagents Nethyl- N-(dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysuccinimide (NHS) were used to formed a intermediated reactive to binding a protein of interest. Significant differences were not observed among the methods, being opted for the lectins immobilization in a single layer using cystamine and glutaraldehyde due to the simple preparation and low consumption of reagents. The formation of self-assembly monolayer formation was studied using the Electroacoustic Admittance, QCM and a flow injection system coupled to QCM. In all studies a cystamine concentration of 15 mmol. L-1 produced the highest frequency variation and therefore the largest observed mass deposition on the gold surface with good repetitivity. However, it was observed a strong interaction between the free cystamine and to that was binding to the gold surface forming a monolayer, but this interaction was not specific. The flow injection system coupled to the QCM technique was also used to study the interaction between the lectin-carbohydrate and lectin-glicoconjugate. This study allows determining that the variation of the quartz crystal frequency was the same magnitude that observed for a system when using a QCM technique. The Langmuir adsorption isotherm was used to calculate the values of the apparent affinity constant for the lectins with different ligands. The apparent affinity constant was 1.4x105 M-1, 9.4x103 M-1 and 5.6x102 M-1 for Jacalin- Fetuin, Jacalin-Galactose and ConA-Maltose interactions respectively. The determinations of the apparent affinity constants using QCM, demonstrated the viability of the technique in the study of molecular interactions.